2005
DOI: 10.1183/09059180.05.00009703
|View full text |Cite
|
Sign up to set email alerts
|

Matrix proteoglycans as effector molecules for epithelial cell function

Abstract: Matrix proteoglycans are complex molecules composed of a core protein and glycosaminoglycan side chains. Once thought to be the molecular glue providing structural support and imparting biomechanical properties to lung tissue, it is now apparent that proteoglycans are important biological modifiers which regulate processes such as lung development, homeostasis, inflammation and wound healing. The diverse roles of proteoglycans in the extracellular matrix suggest that these molecules play a critical role in nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 78 publications
0
18
0
Order By: Relevance
“…Based on our discovery of GAG-binding and GAGbinding-like motifs at site 1 (within the RBD, Y453-S459), site 2 (at the proteolytic cleavage site at S1/S2 junction, P681-S686), and site 3 (at the S2' proteolytic cleavage site, S810-S816), we hypothesized that SARS-CoV-2 may also interact with host cell surface GAGs through its SGPs to invade host cell (Fig 1, S2 Fig, S3 Fig). The predominant GAG in normal human lung is HS followed by CS [22] and it is noteworthy that lung tissue is rich in mast cells and has been a source of commercial HP [23]. Using unbiased docking, we found that TriS HS hexasaccharide 5D).…”
Section: Discussionmentioning
confidence: 94%
“…Based on our discovery of GAG-binding and GAGbinding-like motifs at site 1 (within the RBD, Y453-S459), site 2 (at the proteolytic cleavage site at S1/S2 junction, P681-S686), and site 3 (at the S2' proteolytic cleavage site, S810-S816), we hypothesized that SARS-CoV-2 may also interact with host cell surface GAGs through its SGPs to invade host cell (Fig 1, S2 Fig, S3 Fig). The predominant GAG in normal human lung is HS followed by CS [22] and it is noteworthy that lung tissue is rich in mast cells and has been a source of commercial HP [23]. Using unbiased docking, we found that TriS HS hexasaccharide 5D).…”
Section: Discussionmentioning
confidence: 94%
“…PGs are key components of the ECM of the lung (35) and are characterized by the presence of one or multiple glycosaminoglycan (GAG) side chains covalently linked to a core protein. PGs provide the tissue with many of its characteristic physicochemical properties and control cellular activity (7,15). Evidence to date suggests that many of these biological interactions are properties of the GAG side chains, which play important roles in growth factor signaling, cellular differentiation, morphogenesis, and pathophysiology (17, 19, 21, 28, 36 -38, 41).…”
mentioning
confidence: 99%
“…A growing view is emerging of the lung's extracellular matrix components as regulators of lung physiology, helping in determining epithelial cell phenotype; binding of and subsequent signaling by cytokines, chemokines, and growth factors; and mediating cell proliferation, migration, differentiation, and apoptosis. [16][17][18][19][20][21][22][23] In disease states, degradation products of extracellular matrix components may activate the Toll-like receptor pathways (see later discussion); thus the degradation products may serve as endogenous 18,[22][23][24] Within this gel-like interstitium reside several varieties of interstitial cells (contractile and noncontractile interstitial cells, 25,26 mast cells, plasma cells, and occasional leukocytes). The remainder of the interstitium is The anatomic dead space, as measured by the singlebreath nitrogen dilution technique, is approximately 30% of each tidal volume.…”
Section: Gross and Subgross Organizationmentioning
confidence: 99%